2016
DOI: 10.1128/aem.04096-15
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Histo-Blood Group Antigen-Like Carbohydrates in Lettuce by Human GII.4 Norovirus

Abstract: Human norovirus (HuNoV) genogroup II genotype 4 (GII.4) strains account for about 80% of the gastroenteritis outbreaks in the United States. Contaminated food is a major transmission vehicle for this virus. In humans, pigs, and oysters, histo-blood group antigens (HBGAs) act as attachment factors for HuNoVs. In lettuce, although the virus-like particles (VLPs) of a GII.4 HuNoV were found to bind to cell wall carbohydrates, the exact binding site has not been investigated. Here, we show the presence of HBGA-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“… Tan et al (2015) reported that sialic acids could be used as additional cellular receptors/co-receptor of Tulane virus and HuNoVs. It is known that receptor-like molecules for HuNoVs are present on the surface of produce, oyster gastrointestinal cells and blood cells ( Tian et al, 2006 ; Gao et al, 2016 ; Wang et al, 2017 ), and might facilitate the bioaccumulation of HuNoVs ( Tian et al, 2006 ; Wang et al, 2012 ). HuNoV’s adherence to receptor-like molecules is resistant to washing, which may facilitate its bioaccumulation on produce to reach potentially human-infectious doses despite low-concentration contamination sources ( Wang et al, 2012 ; Zhou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“… Tan et al (2015) reported that sialic acids could be used as additional cellular receptors/co-receptor of Tulane virus and HuNoVs. It is known that receptor-like molecules for HuNoVs are present on the surface of produce, oyster gastrointestinal cells and blood cells ( Tian et al, 2006 ; Gao et al, 2016 ; Wang et al, 2017 ), and might facilitate the bioaccumulation of HuNoVs ( Tian et al, 2006 ; Wang et al, 2012 ). HuNoV’s adherence to receptor-like molecules is resistant to washing, which may facilitate its bioaccumulation on produce to reach potentially human-infectious doses despite low-concentration contamination sources ( Wang et al, 2012 ; Zhou et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [72,88,89] have found HBGA like glycans on glycoproteins and glycolipids in diverse food sources such as oysters, clams, fruits and vegetables. Recently researchers have also found HBGA-like saccharides on the cell wall of lettuce [90]. ABO group determinants were first discovered in the blood.…”
Section: Food Glycans and Antigensmentioning
confidence: 99%
“…MOA 1: The undigested oligoglycans (for example HBGA-like moieties found in food, xenoantigens) form high affinity PCI with soluble (galectins) or membrane-bound human lectins (PRRs) [90,131]. The interaction will impose morphodynamic changes to the transmembrane proteins in the lipid rafts and evoke a biochemical response [132].…”
Section: Glycan Reactionsmentioning
confidence: 99%
“…Since HBGA-like glycans have been found in food items [448], and because microbes bear HBGA-like substances (outside the cell surface) [449], recognition events triggered by PCI or CCI with endogenous lectins are the norm. This cascades in an alignment of food items and microbiota with the genetic constitution of an individual (gut linen) based on an ABO glycophenotype.…”
Section: A Holistic Perspectivementioning
confidence: 99%